Sintesis dan Karakterisasi Katalis Bentonit Termodifikasi TiO2 dan Terinpregnasi Logam Ni : Synthesis and Characterization of TiO2 Modified Bentonite Catalyst and Ni Metal Impregnated - Mirzan, Mohamad; Duda, Nining Austi; Khairuddin; Nurakhirawati; Ruslan (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2024)
TiO2-modified and Ni-impregnated bentonite catalysts have been synthesized and characterized to determine their physicochemical properties. Ni(NO3)2.6H2O was used as a precursor for impregnation. The physicochemical properties determined include surface acidity by acid-base titration method, FTIR spectrum, and XRF and XRD data. The highest surface acidity value was obtained from the Ni-TiO2/bentonite catalyst sample of 1.57 mmol/g. The results of FTIR analysis showed that the peak at wave number 3441 cm-1 in TiO2/bentonite shifted to 3458 cm-1 in Ni-TiO2/bentonite. The distribution of bentonite content after being pillared with TiO2 = 8.68% and impregnated with NiO = 0.58%. The success of nickel metal impregnation into the TiO2/bentonite support was obtained from XRD data, which was marked by the appearance of a typical Ni peak at 2θ = 37.70° d = 2.38 Å, 2θ = 39.39° d = 2.28 Å, 2θ = 43.02° d = 2.10 Å, 2θ = 51.38°d = 1.77 Å.